Nilai Moral pada Syair Suluk Ngaji Jawa (Kajian Sosiologi Sastra) - Mutolib; Onok Yayang Pamungkas (JIMAD: Jurnal Ilmiah Mutiara Pendidikan, 2023)
This research discusses the moral values ​​in Javanese Suluk Poetry under three titles, namely “Serate Pupils”, “Introspection” and “Ojo Dumeh”. In this research the author tries to examine the three suluk titles in everyday life. With social problems becoming more numerous and complicated, this research will relate them to existing social realities and will be linked to the values ​​that exist in Javanese suluk. In this research, we will discuss the moral values ​​of Suluk which are adopted from a literary sociology approach to analyze the moral values ​​contained in Javanese Suluk poetry, especially in two poems entitled “Serate Siswa”, “Introspection” and “Ojo Dumeh” . The focus of this research is on religious, social moral values ​​and human interaction with God as reflected in these literary works. This research uses qualitative methods with descriptive analysis techniques to describe and explore information related to the moral values ​​in the two poems. The results of research on the three titles of Syair Suluk Jawa show that the poem “Serate Disciple” emphasizes the importance of manners, simplicity, and respect for others, by describing the relationship between students and teachers as a reflection of the relationship between humans and God. On the other hand, the poems, “Introspection” and “Ojo Dumeh” highlight the wisdom in looking at age and death, reminding people to continue to worship selflessly, and live life humbly. In conclusion, Suluk Javanese poetry, through sociological analysis of literature, is able to convey a deep moral message regarding human relationships with God and others. This research contributes to the understanding of the moral values ​​contained in Javanese literary works, as well as maintaining and introducing the uniqueness of Javanese culture to society.